PENDIDIKAN AGAMA ISLAM BERWAWASAN PLURALISME - Heri Surikno (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This article contains the urgency of pluralistic Islamic education at schools. In common, the function of educationis an attempt to change the paradigm and social conditions of society towards a better, including the Islamiceducation. In the context of a multicultural and multiethnic country such as Indonesia, the education whichbased on pluralism becomes a necessity. This is understandable when seeing the reality in which the violence inthe name of religion is still rife in this country. The behavior shows, when the education is defined as a processof value’s transformation, education has not succeeded in creating students who are ready to accept diversity,especially diversity of religions and beliefs. This is where Islamic education is considered as an important role. Onthis reason, the article contains a conceptual study is presented for the purpose of presenting the limits and purposesof research to find an educational approach, teaching methods, and the competence of Islamic education teachersinsightful pluralism. Here are a few approaches that can be used, namely the multi perspectives’ approaches,historical approaches, sociological, psychological, aesthetic, dialogical, reflective and expressive approaches. Themethod can be used, among others: the exemplary methods, harvesting, work in group, brainstorming, andcase studies. In terms of competence, teachers who have the ability to teach pluralism are teachers who has anopen attitude, tolerance, active, and able to a ccept differences.